PERSPEKTIF EKONOMI ISLAM ATAS JUAL BELI PAKAIAN BEKAS (THRIFT) - Damara, Dandi; Kholiq, Abdul; Latifah, Eny; Abdullah, Rudi (JIDE : Journal Of International Development Economics, 2023)
This research aims to determine the practice of buying and selling used clothing from an Islamic economic perspective. The research method is a qualitative case study type. The results of the research are that the practice of buying and selling used clothing (thrift) at the Juni Fitri Store in Banjarwati Village consists of the stages of the process of purchasing used clothing stock, determining the type of goods to be sold, determining the selling price, and selling used clothing. The Islamic economic perspective in buying and selling used clothes (thrift) at the Juni Fitri Store, Banjarwati Village, can be seen from Islamic economic values, namely Tauhid, Morals, Justice, Balance, Individual Freedom in various operational forms such as: the process of purchasing used clothing stock, clothing sales mechanisms used clothes, washing and ironing used clothes, photo media for used clothes, determining prices, promotional media for used clothes, and service and sales of used clothes.